E-learning as a Supplemental Teaching Tool for Secondary Students in Uganda: lessons from COVID-19 - Walekhwa, Abel Wilson; Jobanputra, Shivani; Nakazibwe, Brenda; Nantongo, Mary; Opio, Chris Derick; Kantipudi, Suvarna; Masanza, Monica Musenero (ResearchSquare, 2022)
Edubee, a holistic learning approach for Ugandan students is an initiative Pic-Ed. Pic-Ed is an educational company that provides digital learning materials for students, learning management systems for schools and institutions plus examination proctoring tools. The project was undertaken to determine the effectiveness of digital learning platform by Edubee in enhancing the educational level achievement of Senior three students in selected districts in Uganda.
Keywords: Science subjects; Secondary schools; E-learning